Knowledge Attitude and Practices of Mitanin's (Community Health Workers) in Chhattisgarh: Malaria Elimination Perspective - Ranjha, Raju; Yadav, Chander Prakash; Chourasia, Mehul Kumar; Nitika,; Dash, Chinmay Kumar; Kumar, Jitendra (Frontiers in Public Health, 2022)
Background: For the success of any programme, its implementation plays a crucial role. Community health workers are of immense importance for malaria elimination from India. Objective: This study was planned to assess the Knowledge Attitude and Practices (KAP) of mitanins from a malaria elimination perspective and determine the factor affecting their knowledge. Method: Structured interviewer based questionnaire was used to collect the data, and ordinal regression was applied to analyse the data. Results: Only 26% of the Mitanins were having a good KAP score about malaria. Malaria endemicity of area (OR=0.26, 95% CI=0.13-0.50), p<0.001) and education (OR=0.35, 95% CI=0.18-0.69, p=0.002) were the two significant factors affecting the KAP of mitanins . Conclusion: This study shows that prioritising education while recruiting the mitanins and training them in the low endemic areas with focus on malaria, which will help achieve the malaria elimination goal.